2014
DOI: 10.1002/2013ja019598
|View full text |Cite
|
Sign up to set email alerts
|

Saturn's dayside ultraviolet auroras: Evidence for morphological dependence on the direction of the upstream interplanetary magnetic field

Abstract: We examine a unique data set from seven Hubble Space Telescope (HST) “visits” that imaged Saturn's northern dayside ultraviolet emissions exhibiting usual circumpolar “auroral oval” morphologies, during which Cassini measured the interplanetary magnetic field (IMF) upstream of Saturn's bow shock over intervals of several hours. The auroras generally consist of a dawn arc extending toward noon centered near ∼15° colatitude, together with intermittent patchy forms at ∼10° colatitude and poleward thereof, located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…In a parallel study of these images, Meredith et al (2014) found no clear IMF response in the dawn emissions, while patchy auroras observed at higher latitudes in the noon to dusk sector were found to occur for northward but not for southward IMF, thus suggesting a connection with reconnection-related processes at the magnetopause as discussed previously by Radioti et al (2011 and Badman et al (2013). In addition, a prominent patch of polar emissions observed in one image for southward IMF was suggested to be due to high-latitude "lobe reconnection" between the IMF and open tail flux tubes poleward of the dayside cusp (e.g.…”
Section: E S Belenkaya Et Al: Magnetospheric Mapping Of Saturn's Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In a parallel study of these images, Meredith et al (2014) found no clear IMF response in the dawn emissions, while patchy auroras observed at higher latitudes in the noon to dusk sector were found to occur for northward but not for southward IMF, thus suggesting a connection with reconnection-related processes at the magnetopause as discussed previously by Radioti et al (2011 and Badman et al (2013). In addition, a prominent patch of polar emissions observed in one image for southward IMF was suggested to be due to high-latitude "lobe reconnection" between the IMF and open tail flux tubes poleward of the dayside cusp (e.g.…”
Section: E S Belenkaya Et Al: Magnetospheric Mapping Of Saturn's Dmentioning
confidence: 99%
“…Nevertheless, this does not preclude the solar wind interaction from playing an important role in outer magnetosphere dynamics at the giant planets; furthermore, it is known, in particular, that bright auroral emissions extend to very high latitudes in the dawn sector at Saturn in response to strong magnetospheric compressions by the solar wind ). In addition, structured dayside auroral features observed in the post-noon sector have been interpreted as the signatures of time-dependent reconnection and openflux production at the dayside magnetopause, similar to "flux transfer events" at Earth (Radioti et al, 2011Badman et al, 2013;Meredith et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…However, that paper examined only the data from the passes over the southern auroral region, such that here we complete the survey by also examining the northern data. We note that other variable current systems may also generally be present associated with the solar wind interaction [e.g., Cowley et al, 2004a;Southwood and Kivelson, 2009;Radioti et al, 2013;Meredith et al, 2013Meredith et al, , 2014, fixed in local time (LT) principally on the dayside, but since the observations to be discussed here are restricted to a narrow LT sector on the nightside, these will not be considered further here. symbols the current system, and the blue arrowed lines and symbols the perturbation field associated with that current system, while in the ionospheric diagram the red dashed lines show the associated atmospheric/ionospheric flow.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that some observations of reconnection at the dayside magnetopause for northward IMF do nevertheless exist (e.g., McAndrews et al, 2008). Meredith et al (2014) studied the northern polar cap and found that post-noon auroral arcs exist for northward IMF, but not for southward IMF. They suggested that these were associated with low-latitude reconnection occurring for northward IMF.…”
Section: Southward and Northward Imfmentioning
confidence: 99%
“…Taking this argument into account, we conclude that the open model is probably appropriate for northward IMF also. Meredith et al (2014) explained that the absence of FTEs at the Kronian magnetopause was likely due to the different timescales of such phenomena relative to the case of Earth due to the much larger magnetospheric length scales involved. As noted above, the open-closed field line boundaries calculated for the two models using the paraboloid model do not show great difference for northward IMF.…”
Section: Southward and Northward Imfmentioning
confidence: 99%